Hybrid esl learning model for tertiary esl learners - Ravindran, S. (University of Jaffna, 2012)
Time to time various teaching theories and approaches have been introduced to improve English as a second language (ESL) learning and teaching. Researchers introduced numerous teaching methods from grammar translation to communicative competence. Each new method lasted a few years or decades due to various teaching learning difficulties, failures and not suiting the needs of the learners and benefitting them. With the advent of Science and technology it became a vogue to conduct computer assisted language teaching and learning. Yet there are impediments in learning and teaching ESL at all levels. The traditional teaching methods are still followed in the tertiary education including the universities in Sri Lanka. The syllabi are designed according to class room teaching. By introducing a hybrid ESL learning model it is intended to achieve better performance in ESL learning and teaching to be on par with ESL learning and teaching in the other developed countries. One hundred and twenty five first year students from the Faculty of Arts University of Jaffna were selected on a random basis. A qualitative method was used to collect data. This study intends to research on introducing a hybrid ESL learning model to the first year students of the Faculty of Arts. Questionnaires were circulated to the students to gather data. Two modes of teaching were done with the students. One in the traditional manner and the other through computer based teaching and learning. Interviews were conducted with the staff and class room observation is utilized. The findings revealed the fact that the learners and staff benefit very much through a hybrid ESL teaching mode. The research may motivate administrators and teachers to introduce hybrid ESL learning at tertiary level.
Keywords: Hybrid; ESL learning; Tertiary level; ESL learners